2006
DOI: 10.1002/ldr.752
|View full text |Cite
|
Sign up to set email alerts
|

Relating soil electrical conductivity to remote sensing and other soil properties for assessing soil salinity in northeast Thailand

Abstract: Mapping and monitoring of soil salinity is required to establish its areal extent and also to keep track of changes in salinity in order to formulate appropriate and timely management strategies for reclamation and rehabilitation of such soils. Remote sensing data have been increasingly used in soil-salinity studies as they are not only quicker but are also useful for making realistic predictions. A study was conducted in northeast Thailand to understand the relationship of spectral reflectance and physico-che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 12 publications
1
53
0
1
Order By: Relevance
“…This is in part due to the high spatial resolution of the IKONOS images. The selected model in this study showed superiority in the prediction power (R 2 = 0.65) of soil salinity over those reported by Shrestha [27] and Landsat, are economically priced or free, more accessible and typically offer broader spatial coverage than more expensive high spatial resolution imagery. Nonetheless, differences in spatial resolution can have a high impact on predicting soil salinity.…”
Section: The Developed Regressions Modelsmentioning
confidence: 72%
“…This is in part due to the high spatial resolution of the IKONOS images. The selected model in this study showed superiority in the prediction power (R 2 = 0.65) of soil salinity over those reported by Shrestha [27] and Landsat, are economically priced or free, more accessible and typically offer broader spatial coverage than more expensive high spatial resolution imagery. Nonetheless, differences in spatial resolution can have a high impact on predicting soil salinity.…”
Section: The Developed Regressions Modelsmentioning
confidence: 72%
“…Nevertheless, these indices are generally weakly or moderately correlated with soil salinity. In most cases, the correlation coefficient may be less than 0.50 [25,26,30]. This paper incorporated all spectral bands for statistical analysis, and demonstrated the usefulness of the PLSR model for soil salinity retrieval with the ALI-convolved field spectra ( Figure 6).…”
Section: Soil Salinity Retrieval From Multi-spectral Sensor Data Basementioning
confidence: 79%
“…Instead of all spectral bands, a majority of existing studies perform statistical analysis based on selected bands [25] and/or indices generated from band combinations. The commonly used indices can be generated from green/red [26], red/NIR [28], NIR/SWIR [29] and SWIR/SWIR bands [30].…”
Section: Soil Salinity Retrieval From Multi-spectral Sensor Data Basementioning
confidence: 99%
“…The EC values in the greenhouse soil are higher than those in the open-field soil, which can be attributed to the fact that there was no soil leaching due to rainfall that occurred under the greenhouse conditions, and the evaporation of the soil water resulted in salt accumulation (Shrestha, 2006).…”
Section: Discussionmentioning
confidence: 92%